Long-cavity mode-locked thulium-doped fiber laser for high pulse energy - Gene, Jinhwa; Yeom, Dong Il; Kim, Seung Kwan; Lim, Sun Do (Optics and Laser Technology, 2021)
We demonstrate a high pulse energy and low pulse rate 2 µm femtosecond fiber laser potentially applicable to laser surgery and vehicle laser detection and ranging. The laser is configured by a half kilometer long all-fiber ring cavity with two thulium-doped fiber gains deployed separately and is hybrid mode-locked by the coaction of a graphene saturable absorber and nonlinear polarization rotation. Numerical simulations were carried out to back up the mode-locking stability and estimate the maximally extractable pulse energy. We achieved a pulse energy of about 54.6 nJ, to the best of our knowledge the highest as a seed femtosecond pulse, and a pulse rate of 427 kHz, the lowest ever reported. The pulse duration was about 456 fs as measured by an intensity autocorrelator, and the output optical spectrum showed a wide FWHM of about 51.7 nm. We also examined the stability of the laser output over tens of hours.
Keywords: Autocorrelators; Femtosecond fiber lasers; Graphene saturable absorbers; High pulse energy; Laser detection and ranging; Mode-locking stability; Nonlinear polarization rotation; Thulium-doped fibers; Fiber optics; Mode-locked lasers; Nonlinear optics; Optical fiber lasers